ANALISIS PENGARUH CITRA MEREK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA BRIO DI BOGOR - Muhammad Iqbal; Heni Nastiti (ITB AAS INDONESIA, 2022)
The Honda Brio car obtained the highest car sales figure in Indonesia in 2020 but has a lower brand image than its competitors as measured by the Top Brand Index. Based on this background, this study aims to determine, prove, and analyze the effects of brand image, product quality, and price on purchasing decisions for Honda Brio in Bogor. The population in this study is the owner of a Honda Brio car in Indonesia. The number of samples is determined by 75 respondents with the criteria of a Honda Brio car owner in Bogor using the purposive sampling method, and data is collected by distributing questionnaires through Google forms. The analytical techniques used in this research are the descriptive analysis technique and inferential analysis using SmartPLS 3.2.9. The results of the hypothesis test are as follows: (1) brand image has an effect on purchasing decisions of 0.249 positive and significant, (2) product quality has an effect on purchasing decisions of 0.300 positive and significant, and (3) price has an effect on purchasing decisions of 0.295 positive and significant, while the joint contribution is shown by the value of R Square Adjusted, which is 0.606 or 60.6%, while 39.4% by other factors.